2007
DOI: 10.1021/np070038q
|View full text |Cite
|
Sign up to set email alerts
|

Antitrypanosomal Activity of Triterpenoids and Sterols from the Leaves of Strychnos spinosa and Related Compounds

Abstract: Fractionation of an antitrypanosomal lipophilic leaf extract from Strychnos spinosa led to the isolation of eight triterpenoids and sterols in this plant part for the first time. Two of these were found to possess in vitro antitrypanosomal activity, namely, saringosterol (14) and 24-hydroperoxy-24-vinylcholesterol (15), with IC(50) values of 7.8 +/- 1.2 and 3.2 +/- 1.2 microM, respectively. The latter compound was isolated from a plant source for the first time. A comparative study on the antitrypanosomal acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 35 publications
4
79
1
Order By: Relevance
“…It implied that this dosage was not toxic to the experimental animal. Similar results were achieved by [15,16,17] with extracts of strychnos spinosa. Literature from other studies on medicinal plants revealed both extracts contain similar compounds.…”
Section: Discussionsupporting
confidence: 81%
“…It implied that this dosage was not toxic to the experimental animal. Similar results were achieved by [15,16,17] with extracts of strychnos spinosa. Literature from other studies on medicinal plants revealed both extracts contain similar compounds.…”
Section: Discussionsupporting
confidence: 81%
“…Natural products such as alkaloids, terpenes, quinones, and polyphenols found in these extracts have been shown to be potent growth inhibition of T. cruzi (Wright and Pillipson, 1990). Triterpenoids and sterols from the plants are reported to possess antitrypanosomal activity (Hoet et al, 2007). The antitrypanosomal activities of alkaloids like actinodaphine, dicentine, cassythine isolated from Cassytha filiformis (Hoet et al, 2004a) are also found in B. buonopozense and several other alkaloids (Merschjohann et al, 2001) displayed significant in vitro antitrypanosomal activity.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] Cholesterol, β-sitosterol, and ergosterol constitute the main eukaryotic sterols representing the three eukaryotic kingdoms: animals, plants, and fungi, respectively. [3] Cholesterol is considered the main animal sterol, an essential metabolite with an important function for normal cell growth in humans.…”
Section: Introductionmentioning
confidence: 99%